Contrasting effect of recombinant human erythropoietin on breast cancer cell response to cisplatin induced cytotoxicity - Trošt, Nina (Radiology and oncology (Ljubljana), 2012)
Background. Human recombinant erythropoietin (rHuEpo) that is used for the treatment of the chemotherapy-induced anaemia in cancer patients was shown to cause detrimental effects on the course of disease due to increased adverse events inflicting patient's survival, potentially related to rHuEpo-induced cancer progression. In this study, we elucidate the effect of rHuEpo administration on breast cancer cell proliferation and gene expression after cisplatin (cDDP) induced cytotoxicity. Materials and methods. Two breast carcinoma models, MCF-7 and MDA-MB-231 cell lines, were used differing in oestrogen (ER) and progesterone (PR) receptors and p53 status. Cells wer e cultured with or without rHuEpo for 24 h or 9 weeks and their growth characteristics after cDDP treatment were assessed together with expression ofgenes involved in the p53-signaling pathway. Results. Short-term exposure ofbreast cancer cells to rHuEpo lowers their proliferation and reduces cDDP cytotoxic potency. In contrast, long-term exposure of MCF-7 cells to rHuEpo increases proliferation and predisposes MCF-7 cells to cDDP cytotoxicity, but has no effect on MDA-MB-231 cells. MDA-MB-231 cells show altered level of ERK phosphorylation, indicating involvement of MAPK signalling pathway. Gene expression analysis of p53-dependent genes and bcl-2 gene family members confirmed differences between long and short-term rHuEpo effects, indicating the most prominent changes in BCL2 and BAD expression. Conclusions. Proliferation and survival characteristics of MCF-7 cells are reversely modulated by the length of the rHuEpo exposure. On the other hand, MDA-MB-231 cells are almost irresponsive to long-term rHuEpo, supposedly due to the mutated p53 and ER(+)/PR(-) status. The p53 and ER/PR status may predict tumour response on rHuEpo and cDDP treatment.
Keywords: breast; breast cancer; Breast neoplasms; Cell division; Cell survival; Cisplatin; citotoksičnost; cytotoxicity; dojke; Drug therapy; eritropoetin; erythropoietin; Erythropoietin, recombinant; Gene expression; Genes, bcl-2; Genes, p53; rak (medicina); Toxicity; Tumor cells, cultured